(untitled) (Journal of Hama University, 2020)
This research aims to determine the effect of internal factors of microfinance institutions on the return of loan portfolio, through the microfinance institutions in Syria, drawing on a sample of three microfinance institutions during the period (2012:Q3 – 2019:Q3). To achieve the objective of the research the variance analysis was used, in addition to designing a mathematical model composed the return of loan portfolio as a dependent variable, and each of the following as independent variables (Loan to deposit ratio (LTD), the Liquidity ratio, and credit risk) The results of this research showed based on the analysis of the cross-sectional data matrix (Panel -data) of microfinance institutions a sample of the research, using the variance analysis model and fixed effects in the statistical analysis program (Eviews10). Differences of statistical significance of the following (Loan to deposit ratio, the Liquidity ratio, the ratio of credit risk) between microfinance institutions of the research sample. The research also showed a positive moral impact in the Loan to deposit ratio LTD and LTD(-1) on the return of loan portfolio of microfinance institutions in the research sample, research has also shown that there is no moral impact in the Liquidity ratio on the return of loan portfolio in the research sample institutions, in addition to a negative moral impact ratio of credit risk CR(-4) on the return of loan portfolio of the research sample’s microfinance institutions.